A Novel Stick-Slip Type Rotary Piezoelectric Actuator - Yuan Wang; Minglong Xu; Shubao Shao; Siyang Song; Yan Shao (Advances in Materials Science and Engineering)
A novel stick-slip rotary piezoelectric actuator is designed for optical use. The actuator is proposed, fabricated, and tested with the aim of realizing both fine resolution and a long stroke. The dynamic model of the actuator is established, and simulations are performed to discover how the input driving voltage affects the stick-slip motion of the actuator. An experimental system is built to evaluate the performance of the actuator at different frequencies, voltages, and numbers of driving piezoelectric stacks. Experimental results show that the minimal output stepping angle is 3.5 μrad (0.2 millidegrees) under a sawtooth waveform having a voltage of 13 V and frequency of 3000 Hz and that the velocity reaches 0.44 rad/s (25°/s) under a sawtooth waveform having a voltage of 93 V and frequency of 3000 Hz, while the stroke is infinite. The proposed actuator provides stable and accurate rotary motion and realizes a high velocity.